Perinatal Outcome in Women Treated with Progesterone for the Prevention of Preterm Birth: a Meta-analysis - Sotiriadis, Alexandros; Papatheodorou, Stefania; Makrydimas, George V. (My University, 2012)
Objective To quantify the effect on perinatal outcome in women treated with progesterone for the prevention of preterm birth. Methods MEDLINE and SCOPUS searches, including references of the retrieved articles and additional automated search using the 'search for related articles' PubMed function, were used. Randomized controlled trials assigning women at risk for preterm birth to progesterone or placebo were included (both singleton and multiple pregnancies). Outcomes were neonatal and perinatal death, respiratory distress syndrome (RDS), retinopathy, necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH) Grade 3-4, sepsis, admission to the neonatal intensive care unit (NICU) and composite adverse outcome. Results Sixteen studies (singletons, n = 7; twins, n = 7; triplets, n = 2) were included in the meta-analysis. For singleton pregnancies, progesterone reduced the rates of neonatal death (risk ratio (RR) 0.487 (95% CI, 0.290-0.818)), RDS (RR 0.677 (95% CI, 0.490-0.935)), NICU admission (RR 0.410 (95% CI, 0.204-0.823)) and composite adverse outcome (RR 0.576 (95% CI, 0.373-0.891)). No favorable effect was observed in twins; in fact, progesterone was associated with increased rates of perinatal death (RR 1.551 (95% CI, 1.014-2.372)), RDS (RR 1.218 (95% CI, 1.038-1.428)) and composite adverse outcome (RR 1.211 (95% CI, 1.029-1.425)). No significant effect was observed in triplet pregnancies. Conclusion Progesterone administration in singleton pregnancies at risk for preterm birth improves perinatal outcomes, but may actually have adverse effects in multiple pregnancies.
Keywords: Νeonatal outcome; Preterm birth; Progesterone